Biocompatible Au-Fe3O4 Nanoparticle-based Magnetic Resonance Imaging in the Diagnosis of Liver Tumor: Biocompatible Au-Fe3O4 Nanoparticle-based Magnetic Resonance Imaging - Shi, Zhuo; Wang, Peng; Xie, Lizhi; Zhao, Xinming (Cellular and Molecular Biology, 2022)
The study aimed to analyze the value and significance of magnetic resonance imaging (MRI) using biocompatible Au-Fe3O4 nanomaterials in the diagnosis of liver tumors. In this study, 124 patients with liver tumors were selected to perform MRI scanning based on Au-Fe3O4 nanoparticles. The coincidence rate between MRI scanning results and pathological examination results, the detection rate of tumor focus between MRI scanning results and CT detection results were analyzed, to evaluate the diagnostic performance of MRI scanning based on Au-Fe3O4 nanoparticles. The results showed that in the detection of primary tumors, secondary tumors, and focal nodular hyperplasia, the coincidence rate between MRI scanning results and pathological examination results was high, and Kappa values were all greater than 0.8. Compared with the results of CT, the detection rate of tumor lesions smaller than 1 cm by MRI was significantly higher (P<0.05), but there was no significant difference between the two diagnostic methods for tumor lesions larger than 1 cm (P>0.05). Additionally, the accuracy, specificity, and sensitivity of MRI in diagnosing liver tumors were 86.81, 84.29, and 77.27, respectively. Clinically, MRI scanning based on Au-Fe3O4nanoparticles can provide a practical and effective reference for the differential diagnosis of liver tumors.